Generalisasi fq-Derivasi di B-Aljabar - Fitria, Elsi; Gemawati, Sri; Sugianti, Khoirunnisa (UIN Imam Bonjol Padang, 2022)
In this paper, another type of derivation in B-algebra is defined, by defining two self-maps, one of which is a derivation in B-algebra (denoted by d) and the other is called generalization of derivation in B-algebra (denoted by D). Based on this definition, some properties of generalized -derivation and generalized -derivation in B-algebra are constructed, then there is one common property, that is if d and D are identity functions, then D is regular. Then, the concept is used as a reference to define the generalized -derivation in B-algebra. In the last section, we discuss some properties of generalized -derivations in B-algebras.